Can commercial farming promote rural dynamism in sub-Saharan Africa? Evidence from Mozambique - Steven M. Glover; Sam Jones (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
The impact of large commercial farms on neighbouring smallholders in low-income sub-Saharan Africa remains controversial. Bringing evidence to a largely anecdotal debate, we deploy a dataset covering all commercial farms in Mozambique, linking them to a nationally representative survey of smallholders. We investigate: (i) the degree of selection of commercial farms into more/less favourable locations; and (ii) the effects of these farms on the incomes of neighbouring smallholders. We are unable to find robust evidence of either positive or negative spillovers from commercial farms. However, certain types of commercial agricultural ventures - outgrower schemes, plantations - appear to generate moderate local welfare gains.
Keywords: O13; Q12; Q18; 330; agriculture; commercial farming; Mozambique; structural transformation